Gastroprotective effects of Prunus laurocerasus L. fruit extracts against the oxidative stress induced by indomethacin in rats - Aydin Berktas, Ozlem; Keskin, Arif; Gulec Peker, Emine Gulceri (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Prunus laurocerasus L. is a perennial plant belonging to the Rosaceae family and is grown on the shores of the Black Sea Region. In the current study, the effect of P. laurocerasus fruits was investigated in the ulcer model created by the application of indomethacin to rats. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Rats divided into five groups: fruit water extract (200 mg/kg), fruit ethanol-water extract (200 mg/kg), lansoprazole agent (LAN, 25 mg/kg), and indomethacin (IND, 25 mg/kg). All administrations were given to animals by oral gavage. At the end of the experiment, macroscopic and biochemical measurements were made in rats. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The lipid peroxidation was quite high in rat stomach tissues given IND. The applied LAN and extracts reduced this increase to almost a healthy rate. On the other hand, the amount of glutathione, catalase, and superoxide dismutase activities were found very low in IND applied tissues. The LAN and fruit extracts treatments tried to show their protective feature by increasing this decreased antioxidant level in their own groups. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The data obtained determined that both enzyme and non-enzyme antioxidant markers measured in fruit extracts had a protective effect almost as strong as lansoprazole.